(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information on the formation of axiological worldview of students based on aesthetic education in pedagogical activities in the modern educational system and on strengthening the spiritual education of students based on national values in the modern pedagogical education program. The main goal will be to increase the moral and educational culture of students and to increase their spiritual maturity, as well as to increase their axiological worldview. Based on these studies, opinions and opinions of experienced pedagogues-psychologists in the Republic of Uzbekistan were used. A team of pedagogues was organized and the pedagogues expressed their opinions on the formation of a broad outlook, high spirituality, and the ability to think freely in students.